Fathers' Experiences and Perspectives of Breastfeeding: A Scoping Review. Issue 3 (15th May 2019) - Sihota, Harvinder; Oliffe, John; Kelly, Mary T.; McCuaig, Fairleth
During the transition to parenthood, fathers may experience significant challenges, including finding a place for themselves as important participants in the context of infant breastfeeding by female partners. Although generally viewed as a healthy process and the preferred method of infant feeding, breastfeeding may result in some fathers feeling excluded, inadequate, and helpless. Breastfeeding is known to adversely affect various aspects of a father's life, including parenting self-efficacy, quality of life (QOL), the relationship with the partner, and the perception that breastfeeding limits time available for father–infant bonding. The current scoping review explores the experiences, roles, and needs of fathers of breastfed infants by synthesizing and discussing the findings from relevant published research studies ( n = 18). Recommendations, drawn from the scoping review findings, are offered to guide primary health providers and services.